Salivary Gland Secretory Carcinoma: A Case Report Emphasizing Cytology, Histopathology, and Immunohistochemistry (GAIMS Journal of Medical Sciences, 2023)
Secretory Carcinoma (SC) or Mammary Analogue Secretory Carcinoma (MASC) is a recently described tumour of the salivary gland that shares morphological and genetic characteristics with secretory carcinoma of the breast. Due to their complex and heterogeneous presentations, majority of these tumors were previously histologically diagnosed as acinic cell carcinoma or mucoepidermoid carcinoma. Here, we present a case of secretory carcinoma of the parotid gland in a 29-year-old female and discuss the cytological, histological and immunohistochemical characteristics that can be used to diagnose the condition and distinguish it from its histologic mimics.